Novel Pyridine‐Containing Sultones: Structure‐Activity Relationship and Biological Evaluation as Selective AChE Inhibitors for the Treatment of Alzheimer's disease. (22nd June 2021) - Zhang, Hong; Wu, Chengyao; Chen, Xing; Zhang, Ziwen; Jiang, Xia; Qin, Hua‐Li; Tang, Wenjian
Abstract: Novel pyridine‐containing sultones were synthesized and evaluated for their cholinesterase (ChE) inhibitory activity. Most of compounds showed selective acetylcholinesterase (AChE) inhibitory activity. The structure‐activity relationship (SAR) showed: (i) the fused pyridine‐containing sultones increase AChE inhibition, series B >series A ; (ii) for series A, the effect of the 4‐substituent on AChE activity, p ‐> m ‐ or o ‐; (iii) for series B, a halophenyl group increase activity. Compound B4 (4‐(4‐chlorophenyl)‐2, 2‐dioxide‐3, 4, 5, 6‐tetrahydro‐1, 2‐oxathiino[5, 6‐ h ]quinoline) was identified as a selective AChE inhibitor (IC50 =8.93 μM), and molecular docking studies revealed a good fit into Tc AChE via hydrogen interactions between the δ‐pyridylsultone scaffold with Asp72, Ser122, Phe288, Phe290 and Trp84. Compound B4 showed reversible and non‐competitive ( K i =7.67 μM) AChE inhibition, nontoxicity and neuroprotective activity. In vivo studies confirmed that compound B4 could ameliorate the cognitive performance of scopolamine‐treated C57BL/6 J mice, suggesting a significant benefit of AChE inhibition for a disease‐modifying treatment of AD. Abstract : Sultones of swing : Compound B4, with a fused pyridine‐containing sultone, was identified as a selective acetylcholinesterase inhibitor (IC50 =8.93 μM), and was found to significantly ameliorate scopolamine‐induced cognitive impairment. This compound has the potential for further development into promising therapeutics for the treatment of Alzheimer's disease.